2021
DOI: 10.3390/ijms222011152
|View full text |Cite
|
Sign up to set email alerts
|

Atractylodin Suppresses TGF-β-Mediated Epithelial-Mesenchymal Transition in Alveolar Epithelial Cells and Attenuates Bleomycin-Induced Pulmonary Fibrosis in Mice

Abstract: Idiopathic pulmonary fibrosis (IPF) is characterized by fibrotic change in alveolar epithelial cells and leads to the irreversible deterioration of pulmonary function. Transforming growth factor-beta 1 (TGF-β1)-induced epithelial-mesenchymal transition (EMT) in type 2 lung epithelial cells contributes to excessive collagen deposition and plays an important role in IPF. Atractylodin (ATL) is a kind of herbal medicine that has been proven to protect intestinal inflammation and attenuate acute lung injury. Our st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The main manifestations of EMT are the down‐regulated epithelial phenotype and increased mesenchymal phenotype. EMT markers include the proteins associated with cell junctions (loss of the epithelial marker E‐cadherin and increase of N‐cadherin) and cytoskeletal proteins (the increase of vimentin and fibronectin) (Chang et al, 2021; Willis & Borok, 2007). TGF‐β1 is an inducer of EMT in a variety of epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…The main manifestations of EMT are the down‐regulated epithelial phenotype and increased mesenchymal phenotype. EMT markers include the proteins associated with cell junctions (loss of the epithelial marker E‐cadherin and increase of N‐cadherin) and cytoskeletal proteins (the increase of vimentin and fibronectin) (Chang et al, 2021; Willis & Borok, 2007). TGF‐β1 is an inducer of EMT in a variety of epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…45) Furthermore, atractylodin, a component of Atractylodis lanceae rhizoma, decreased NO production and mRNA levels of iNOS, TNF-α, CCL2, and LCN2 in IL-1β-treated hepatocytes, 46) inhibited the increase in mRNA levels of type I and type III collagen by TGF-β1 treatment in A549 cells, and reduced bleomycin-induced pulmonary fibrosis in mice. 47) Cinnamic acid, a component of Cinnamomi Cortex, downregulated NOX2 gene expression in PMA-stimulated THP-1 cells, subsequently reducing the expression levels of inflammatory mediators, such as IL-1β, IL-8, CCL5, and cyclooxygenase (COX)-2, suggesting that it has antioxidant and anti-inflammatory effects. 48) Dehydrotumulosic acid and pachymic acid, components of Hoelen, have been shown to inhibit LTB4 release from human leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Atractylodin, a heterocyclic compound, is also a major active ingredient of ALR. Numerous pharmacological experiments, both in vivo and in vitro , have demonstrated that atractylodin possesses several activities, including anti-inflammatory, anti-tumor and liver protective effects ( Tang et al., 2018 ; Chuang et al., 2019 ; Chang et al., 2021 ). In addition, our present study also identified ketones and esters.…”
Section: Discussionmentioning
confidence: 99%
“…Atractylodin has been demonstrated to have anti-tumor, anti-bacterial, anti-viral, anti-arrhythmia effects, particularly on the nervous system and alimentary canal. Thus, it has been considered as one of the major constituents of ALR ( Chae et al., 2016 ; Ma et al., 2019 ; Chang et al., 2021 ). Sesquiterpene compounds are the major bioactive agents in ALR essential oil.…”
Section: Introductionmentioning
confidence: 99%